Potential Antibacterial Of Leaves And Flowers Bougenvillea (Bougenvilea Glabra) - Priyanto Dwi Nugroho; Faisal Ismail; Hana Relita (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2017)
High incidence of antibiotics resistant bacteria spurred researchers to obtain alternative antibacterial compounds. One source of potential antibacterial compounds i.e plants. Bougainvillea (Bougenvillea glabra) has been believed by the people of Indonesia to have medicinal properties, but its potential as an antibacterial has never been studied in Indonesia. The aims of this study were to determine the bioactive compounds ethanol extract of leaves and flowers of B. glabra as well as the minimum concentration of extract capable of inhibiting and killing bacteria growth. Minimum Inhibition Concentration (MIC) was done used microdilution method and Minimum Bactericidal Concentration (MBC) agar plate method. Ethanol extract of leaves and flowers of B. glabra possess antibacterial activity against pathogenic bacteria; Bacillus sp., S. aureus, Salmonella sp., E. coli, P. aeruginosa and K. pneumoniae. Salmonella, Bacillus sp., and S. aureus growth is most vulnerable (p<0.05). The antibacterial activity of leaf and flower extracts was not significantly different (p>0.05) against all test bacteria. Antibacterial potency of leaves and flowers B. glabra suspected of flavonoids, tannins, terpenoids and alkaloids